The Malaysia IT Outsourcing industry skill-sets requirements of future IT graduates - Ahlan, Abdul Rahman; Arshad, Yusri; Suhaimi, Mohd Adam; Hussin, Husnayati (World Scientific and Engineering Academy and Society, 2010)
IT changes very quickly and influences business, industry and the public in an enormous manner. The issue of IT outsourcing (ITO) impact on IT workforce has been discussed widely in many developed countries so much so that the concerns have been tense in that more IT jobs will be transferred to developing countries which provide IT outsourcing services. In addition, with the growth of IT outsourcing and emerging new outsourcing business models such as utility demand, application service provider, business process outsourcing, offshore outsourcing and many more servicing different industry vertical sectors increase the demand for multiple IT skills and capabilities of IT workforce. In this study, we review relevant literature, newspapers and non-academic articles, websites of companies, governments and nongovernmental organisations and others. An outsourcing Malaysia (OM) CEO roundtable discussion is also held to get inputs from the practitioners on the topic. In addition, we seek in-depth insights from seven senior executive managements in service provider firms on the skill sets requirements of fresh IT graduates to fulfill the market needs of IT outsourcing in Malaysia. The four-member research team found that technical, soft and problem-solving skills are the main concerns raised by the key informants. This is in line with the literature review and also the present higher education policy concerns by the Malaysia government. Keywords: Malaysia, IT outsourcing, skill-sets, workforce, curriculum, developing country